Effect of Cement Dust on Pulmonary Functions of Cement Workers - Hashemi, Reza; Sadeghi, Mahmoud; Khomar, Abdolali; Mirzaei, Ramezan; Aliakbari, Fereshteh; Shariatpanahi, Samira (Archives of Men’s Health, 2020)
Background: Among cement dust, quartz particles are the most harmful and cause pulmonary fibrosis, which is pathologically among the severe and malignant pneumoconioses. Therefore, by measuring the dust and examining the status of lung functions among workers, we can assess the effects of inhaling cement dust. We aimed to assess the effect of cement dust on pulmonary functions among cement workers during 1999-2000 in Khash, Sistan and Baluchestan Province, Iran. Material and Methods: The total and inhalation dust of the working environment of different units in this industry was measured by individual sampling pump and silicon by weight method and after correcting the volumes, mg/m3 of dust was calculated. Results: The total dust in different environments was 6.8-95 mg/m3 and the inhaled dust was 2.5-23 mg/m3. Due to the percentage of free silica associated with dust, these values are several times the standard values in the workplace. The mean values of respiratory functions (FEV1, FVC, VC) in all cases were lower (P-value<0.005) than the mean values in the control group. The difference in the mean FEF25-75 values between the two groups was not significant (P-value>0.5). Although in the case group (all types of workers) the percentage of people with cough was more than the control group, the difference was not statistically significant (P<0.05). With respect to having sputum in the morning and during the day and night and the type of sputum (green and thick, thin, and no sputum), the case group experienced higher rates of sputum and respiratory symptoms. Conclusion: The working environments of cement factories, contrary to what is stated in the toxicology textbooks, requires more attention of health experts and industry managers. Examinations and periodic dust control measures and hiring an occupational health expert is necessary to maintain the health of workers in these environments.